Isomerization and hydrocracking of n-decane over magnesium-containing molecular sieves with AEL, AFI, and AFO topology - Hartmann, Martin; Elangovan, S. (Chemical Engineering & Technology, 2003)
Isomerization and hydrocracking of n-decane have been studied over magnesium-containing molecular sieves with different pore width. A high selectivity for n-decane isomerization is observed over 0.5Pt/MgAPO-11, while hydrocracking is dominant over 0.5Pt/MgAPO-5. The observed high selectivity for n-decane isomers over 0.5Pt/MgAPO-11 and 0.5/MgAPO-41 catalysts is primarily a consequence of the shape selective properties of these medium pore molecular sieves with AEL und AFO topology. The formation of bulky dibranched and tribranched isomers, which are preferentially cracked (i.e., faster), is restricted by the small pore width. The high selectivity for methyl nonanes observed over 0.5Pt/MgAPO-11 allows the assumption that these catalysts are also suitable for the isomerization of C to C alkanes with the aim of improving the low-temperature properties of diesel fuels or lube oils.